ARTIKULASI KEPENTINGAN MASYARAKAT DESA SEI MENCIRIM KEPADA PEMERINTAH DALAM PENYELESAIAN TUMPANG TINDIH LAHAN TAHUN 2017-2021 - Rika Ramadani Sembiring; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Articulation of community interests is the activity of a group of people who have a goal to unite to achieve a common goal. In the process of articulating the interests of the community, they carry out movements or actions to convey demands to the government. So that people get the policies they want. Alternative dispute resolution outside the court by means of arbitration and mediation, in which there is an arbitration agreement made by the parties, is carried out by discussing the differences that arise between the disputing parties through "consensus deliberation" with the aim of achieving a win-win solution. The research method used is a qualitative method by explaining descriptive data. The type of research data used is primary in the form of data obtained from research informants and secondary in the form of data obtained from related documents. Then, the location of this research was carried out in Sei Mencharim Village, Kutalimbaru District, Deli Serdang Regency, North Sumatra. The results of this study are to determine the process of articulating the interests of the Sei Mencharim community to the government and the demands of the community to the government, and government policies in resolving overlapping lands that occur between Sei Mencharim Village and PTPN II. Keywords: Demonstration, Mediation, Arbitration